Pandangan Horace Bushnell Tentang Pendidikan Kristiani Dan Relevansinya Bagi Keluarga Di Zaman Kontemporer - Senda, Siprianus Soleman; Hendriko Dicky Tae Della; Yohanes Subani; Petrus Nandi (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
The discourse on education becomes urgent and important when we witness various forms of humanitarian problems that challenge our conscience. These issues are becoming increasingly complex and intricate in this contemporary era. Meanwhile, the existence of social institutions, particularly the family, is also being questioned. Questions arise about how families should play a role in educating and nurturing the attitudes and character of children to become good human beings. To address this, this article seeks to offer Horace Bushnell's thoughts on education or Christian nurturing. The research method used is library research with descriptive analysis. Research findings indicate that Christian education within the family shapes children with integrity, who are religiously devout and morally correct. Additionally, it was also found that the role of parents in educating children within the family can protect children from social problems in today's contemporary age. The main purpose of this article is to introduce Horace Bushnell's thinking on Christian education in the family and to find practical implications in an effort to overcome the various practical challenges of Christian families in contemporary times. Keywords: Horace Bushnell, Education, Christian, Family, Contemporary